Using Information And Communication Technologies To Improve Transparency In Transition Countries - Mysore Ramaswamy (European Scientific Journal, ESJ, 2016)
Automating government to citizen (G2C) interactions will help in achieving transparency and combating corruption. However, in the case of post-communist transitioning countries such as Armenia, the challenges are unique. These countries are struggling with the transformation of their legacy bureaucratic and administrative processes. In addition, almost every post- Soviet country has inherited systemic corruption that is built in to the ‘modus operandi’ of both the public and private sectors. The process of automating G2C interactions using information and communication technology (ICT) needs to be analyzed as a socio-technical information processing system. Automating existing bureaucratic processes that are defective will not yield results. Improving the enforcement of rules through automation is clearly the best way to combat corruption. The introduction of e-Government plays a major role in this context as it automates several processes. To deliver public service in a more transparent and efficient way, it is necessary to categorize, assess, and modify existing administrative processes. In this paper, we propose a methodology to render transparency in governance using information and communication technology that goes beyond mere automating existing citizen-government interactions.